THE EFFECT OF MARKET STRATEGY ON MARKETING PERFORMANCE OF SMALLHOLDER RUBBER FARMERS IN CENTRAL KUANTAN DISTRICT, KUANTAN SINGINGI REGENCY - Elizabet Sona Br Tambunan; Shorea Khaswarina; Yeni Kusumawaty (Agricultural Socio-Economics Journal, 2022)
This study aims to analyze the effect of market strategy on marketing performance in smallholder rubber in Kuantan Tengah District, Kuntang Singingi Regency, Riau. These market strategies include market shaping strategies, customer engagement strategies, and technology leadership strategies. The population in this study found 225 people from 1 Gapoktan and 9 farmer groups in Kuantan Tengah District. The research sample was 15% of the population, namely 34 people who were selected by random sampling method. Data analysis used descriptive analysis and multiple linear regression models. The results of the analysis show that the respondent's level of achievement reaches 80,82% for market strategy and 74,22% for marketing performance, both of which are in the good level category. The value of sig.t for X1 is 0.861, the value of sig.t for X2 is 0,342, the value of sig.t for X3 is 0,585 is greater than the significance level (α), then the formation of market strategy, customer involvement, and technology leadership partially have no significant effect. significant to marketing performance. The sig.F value of 0,728 is higher than the significance level (α), so the formation of market strategy, customer involvement, and technology leadership simultaneously do not have a significant effect on marketing performance.